Różnice kulturowe jako obiekt badań - Clijsters, Willy (Intercultural Differences : Which Basis?, 2008)
T. Hall, G. Hofstede, F. Trompenaars and others gave a pragmatic definition of "culture" not as a collection of arts but as a set of values and beliefs that belong to everyone's daily life. On this basis, they did a lot of research about the impact of "culture" in international business. A researcher as Hofstede has even tried to rank for the most important nations four and later five so called dimensions of culture. But has a nation a homogeneous business culture? How static is it? How useful are the findings of research? How can we refine them? Does the Anglo-Saxon economic domination induce everyone to an aseptic international business culture? Or does a business (wo)man keep her/his own set of values, beliefs ... even when he/she is speaking English? Does he/she speak English or do we have to speak about Swenglish (Sweden), Frenglish (France), Denglish (Netherlands), Penglish (Poland) ..,? In one word, is globalization inherent to business but far away from business communication?
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 99-105